2007
DOI: 10.1096/fj.07-9420com
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of xenon: a therapeutic window of opportunity in rats subjected to transient cerebral ischemia

Abstract: Brain insults are a major cause of acute mortality and chronic morbidity. Given the largely ineffective current therapeutic strategies, the development of new and efficient therapeutic interventions is clearly needed. A series of previous investigations has shown that the noble and anesthetic gas xenon, which has low-affinity antagonistic properties at the N-methyl-D-aspartate (NMDA) receptor, also exhibits potentially neuroprotective properties with no proven adverse side effects. Surprisingly and in contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
92
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 58 publications
10
92
1
3
Order By: Relevance
“…Xenon is a noble gas which crosses the blood-brain barrier and is already used for anaesthesia in the clinical setting. It is a partial NMDA receptor antagonist, but also has anti-apoptotic properties 195,196 . Animal studies have shown an additive neuroprotective effect of therapeutic hypothermia combined with inhalation of xenon gas after hypoxia-ischaemia 192,[197][198][199][200] .…”
Section: Combination With Pharmacological Agentsmentioning
confidence: 99%
“…Xenon is a noble gas which crosses the blood-brain barrier and is already used for anaesthesia in the clinical setting. It is a partial NMDA receptor antagonist, but also has anti-apoptotic properties 195,196 . Animal studies have shown an additive neuroprotective effect of therapeutic hypothermia combined with inhalation of xenon gas after hypoxia-ischaemia 192,[197][198][199][200] .…”
Section: Combination With Pharmacological Agentsmentioning
confidence: 99%
“…The inert anesthetic gas xenon has received increasing interest as a neuroprotectant over the last decade. Xenon has proven to be neuroprotective both in vivo and in vitro with minimal adverse effects (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). We and others have previously reported that adding immediate xenon to HT enhanced the neuroprotective effects of HT after induced hypoxia-ischemia in neonatal rats (12,13,15,20) and newborn pigs (21).…”
mentioning
confidence: 97%
“…These two gases produce the same effect than memantine, a low-affinity antagonist of NMDA receptor which is already used in clinics for neurodegenerative disease treatments (David et al, 2006). Investigations in rodents have confirmed that xenon at subanesthetic concentrations of about 50 vol% provides maximal neuroprotection, even when given 2 to 4 h after the insult onset Dingley et al, 2006;David et al, 2008). Nitrous oxide and argon (David et al, submitted) which are less expensive gases than xenon, possess mild-to-moderate neuroprotective properties against excitotoxic insults and hypoxicischemic injuries.…”
mentioning
confidence: 98%
“…When administrated after the reperfusion, xenon has beneficial effect by suppressing ischemic brain damage and tPA-induced brain hemorrhages Protein-Noble Gas Interactions Investigated by Crystallography on Three Enzymes -Implication on Anesthesia and Neuroprotection Mechanisms 287 (David et al, 2010) while nitrous oxide reduces ischemic brain damage but increases tPAinduced brain hemorrages (Haelewyn et al, 2011). Xenon is thus a very promising neuroprotective drug with few or no adverse side effects in models of acute ischemic stroke or perinatal hypoxia-ischemia (Homi et al, 2003;Ma et al, 2003;Abraini et al, 2005;David et al, 2008;Luo et al, 2008). Despite this, the widespread clinical use of xenon is limited by its scarceness and excessive cost of production, even if close xenon delivery systems are now being developed.…”
mentioning
confidence: 99%